EXPLORING THE EFFECTS OF FINANCIAL TECHNOLOGY ON SMALL BUSINESS GROWTH: A QUALITATIVE LITERATURE REVIEW - Hatma, Ramli (Penerbit Lafadz Jaya, 2024)
This qualitative literature review investigates the effects of financial technology (fintech) on the growth of small businesses, aiming to synthesize existing research and identify key themes and insights. The study examines how various fintech innovations, such as mobile payments, digital lending, and online banking, influence the operational efficiency, financial accessibility, and overall growth trajectory of small enterprises. The review also highlights the role of mobile payment systems in streamlining transactions, reducing costs, and improving cash flow management for small businesses. These systems enable businesses to accept a wider range of payment methods, cater to a broader customer base, and increase sales. Moreover, the adoption of online banking and digital financial management tools is found to enhance operational efficiency by simplifying financial processes, facilitating better financial planning, and providing real-time financial insights. Despite the numerous benefits, the study identifies challenges such as digital literacy, cybersecurity risks, and regulatory compliance as significant barriers to the full adoption of fintech by small businesses. The literature emphasizes the need for supportive policies, education, and technological infrastructure to overcome these challenges and maximize the benefits of fintech for small enterprises. In conclusion, fintech has a profound impact on the growth and sustainability of small businesses by improving financial accessibility, operational efficiency, and competitive positioning. Future research should focus on longitudinal studies to evaluate the long-term impacts of fintech adoption and explore the effectiveness of policy interventions aimed at supporting small business integration into the digital financial ecosystem.